Gregor Tarco from Litovel, Latin Poet of Renaissance Humanism - Kolářová, Jana (Bohemica Olomucensia, 2017)
The study deals with the work of the poet from Litovel, Gregor Tarco, who lived in the 16th century in the period of late renaissance humanism. The study focuses not only on his main work, the German poem "Beschreibung der Stadt Lüttau", but also on his small Latin poems, so called epithalamia. The article analyses the poems and asks questions about the reasons of author's bilingualism too.
Keywords: Gregor Tarco; 16th century; Latin poetry in Moravia